Pengaruh Likuiditas, Profitabilitas, dan Pertumbuhan Aset Terhadap Struktur Modal: (Studi Pada PT. Indofood Sukses Makmur, Tbk. yang Terdaftar di Bursa Efek Indonesia pada Periode Tahun 2010-2017) - marselia Purnama; Octavianti Purnama (Komunitas Dosen Indonesia, 2020)
PT. Indofood Sukses Makmur, Tbk. known as a leading company in each of its business categories. As a leading company, one aspect that must be considered by this company is capital, because without capital of each company will not be able to carry out activities that are in accordance with the objectives set by the company.This study aims to determine the effect of liquidity (Current Ratio), profitability (Return On Assets), and growth of assets to capital structure (Debt to Equity Ratio) at PT. Indofood Sukses Makmur, Tbk. listed on the Indonesia Stock Exchange in the period 2010-2017.The data analysis technique used in this study is multiple linear regression analysis with the help of computer software, namely SPSS 25 and with Microsoft Excel. The results of this study indicate that the Current Ratio has a negative and significant effect on Debt to Equity Ratio, Return On Assets has a positive and not significant effect on Debt to Equity Ratio, and asset growth has a positive and not significant effect on Debt to Equity Ratio.The conclusion of this study is the variable CR, ROA, and AG simultaneously influence the DER variable